High-Performance Design of a 4-Bit Carry Look-Ahead Adder in Static CMOS Logic - Mehedi Hasan; Abdul Hasib Siddique; Abdal Haque Mondol; Mainul Hossain; Hasan U. Zaman; Sharnali Islam (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2020)
Design of a 4-bit Carry Look-Ahead (CLA) process in static CMOS logic has been presented. CLA architecture proposed in this work computes carry-out terms without using carry-propagate and carry-generate signals which are used in conventional static CMOS (C-CMOS) 4-bit CLA adder. Performance parameters of the proposed 4-bit CLA architecture have been simulated and validated by comparing with the conventional design using Cadence design toolset in 45 nm technology. The designs were compared in terms of average power consumption, propagation delay and power delay product (PDP). The proposed 4-bit CLA topology obtained 34.53 % improvement in speed, 4.84 % improvement in power consumption and 37.696 % improvement in PDP while the source voltage was 1.0 V. Hence, as per acquired simulation results, the proposed 4-bit CLA structure is proven to be an excellent alternative to the conventional design for data-path design in modern high-performance processors.Design of a 4-bit Carry Look-Ahead (CLA) process in static CMOS logic has been presented. CLA architecture proposed in this work computes carry-out terms without using carry-propagate and carry-generate signals which are used in conventional static CMOS (C-CMOS) 4-bit CLA adder. Performance parameters of the proposed 4-bit CLA architecture has been simulated and validated by comparing with the conventional design using Cadence design toolset in 45 nm technology. The designs were compared in terms of average power consumption, propagation delay and power delay product (PDP). The proposed 4-bit CLA topology obtained 26.67 % improvement in speed, 5.966 % improvement in power consumption and 31.06 % improvement in PDP while the source voltage was 1.0 V. Hence, as per acquired simulation results, the proposed 4-bit CLA structure is proven to be an excellent alternative to the conventional design for data-path design in modern high-performance processors.